The Impact of Parenting Style on Attitudes toward Masturbation: A Latent Profile Analysis. Issue 6 (18th October 2021) - Klukas, Ethan; Draper, Emily; Kaseweter, Kimberley; Gregoire, Nina; Cioe, Jan
Abstract: Parents play a vital role in the development of their children's sexual attitudes and behaviors; however, little is known about the impact of parenting on masturbation attitudes. The present study aimed to explore the role of discussions with parents about attitudes toward masturbation. Additionally, latent profile analysis (LPA) was used to determine whether subgroups of exposure to distinct parenting styles exist, and if so, the extent to which they are related to the formation of masturbation attitudes. A convenience sample of 279 university students aged 18–21 completed an anonymous self-report survey. Participants who had not discussed masturbation with their parents reported significantly more negative attitudes than those who had discussed it. In general, participants who perceived their parents to be high in both rejection and control reported more negative attitudes toward masturbation than participants whose parents were lower in rejection and lower in control. The LPA revealed three parenting profiles that were differentially related to young adults' masturbation attitudes: Permissive Parenting, Typical Parenting, and Authoritarian Parenting. An exploratory analysis found that female participants endorsed fewer negative attitudes toward masturbation than their male counterparts. Bayesian statistics were used to improve the interpretation of the data, allow for more meaningful and accurate conclusions, and provide converging evidence with the null hypothesis significance testing results. Implications and limitations are discussed within the context of current masturbation and parenting style research.